2022
DOI: 10.1186/s12885-022-09213-z
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric analysis of radiation-induced brainstem necrosis for nasopharyngeal carcinoma treated with IMRT

Abstract: Background Radiation-induced brainstem necrosis (RIBN) is a late life-threatening complication that can appear after treatment in patients with nasopharyngeal carcinoma (NPC). However, the relationship between RIBN and radiation dose is not still well-defined. Methods During January 2013 and December 2017, a total of 1063 patients with NPC were treated at Sichuan cancer hospital with IMRT. A total of 479 patients were eligible for dosimetric analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In a study by Andruska et al [ 5 ], a large fraction dose of 30 Gy/5 fractions for brain metastasis resulted in a 15% incidence of RN, which occurred at a median of 6.9 months after treatment. In contrast, smaller fraction doses with a higher number of fractions (5,500–7,500 cGy/30–36 fractions) were associated with a 1.3% incidence of brainstem necrosis at a median of 28.5 months after intensity-modulated RT for nasopharyngeal cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Andruska et al [ 5 ], a large fraction dose of 30 Gy/5 fractions for brain metastasis resulted in a 15% incidence of RN, which occurred at a median of 6.9 months after treatment. In contrast, smaller fraction doses with a higher number of fractions (5,500–7,500 cGy/30–36 fractions) were associated with a 1.3% incidence of brainstem necrosis at a median of 28.5 months after intensity-modulated RT for nasopharyngeal cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cheng-Yun Yao et al [39] analyzed 327 patients with NPC undergoing IMRT and discovered that 8 had brainstem damage caused by radiation. Xi-Gang Fan et al [40] discovered that radiation-induced brainstem necrosis was identified in 6 out of 479 NPC patients. The maximum brainstem dose was discovered to be greater in individuals with radiation-induced brainstem necrosis than in those without the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng-Yun Yao ( 36 ) et al reviewed 327 patients with NPC receiving IMRT and found that 8 patients had radiation-induced brainstem injuries. Xiang Fan et al ( 37 ) found that among 479 patients with NPC, six patients were diagnosed with RT-induced brainstem necrosis. They found the maximum dose (D max ) of the brainstem in patients with RT-induced brainstem necrosis was greater than that in patients without necrosis.…”
Section: Discussionmentioning
confidence: 99%